Effects of an Inquiry-Based Short Intervention on State Test Anxiety in Comparison to Alternative Coping Strategies - Krispenz, Ann; Dickhäuser, Oliver (Frontiers in Psychology, 2018)
Background and Objectives: Test anxiety can have undesirable consequences for learning and academic achievement. The control-value theory of achievement emotions assumes that test anxiety is experienced if a student appraises an achievement situation as important (value appraisal), but feels that the situation and its outcome are not fully under his or her control (control appraisal). Accordingly, modification of cognitive appraisals is assumed to reduce test anxiety. One method aiming at the modification of appraisals is inquiry-based stress reduction. In the present study (N = 162), we assessed the effects of an inquiry-based short intervention on test anxiety. Design: Short-term longitudinal, randomized control trial. Methods: Focusing on an individual worry thought, 53 university students received an inquiry-based short intervention. Control participants reflected on their worry thought (n = 55) or were distracted (n = 52). Thought related test anxiety was assessed before, immediately after, and two days after the experimental treatment. Results: After the intervention as well as two days later, individuals who had received the inquiry-based intervention demonstrated significantly lower test anxiety than participants from the pooled control groups. Further analyses showed that the inquiry-based short intervention was more effective than reflecting on a worry thought but had no advantage over distraction. Conclusions: Our findings provide first experimental evidence for the effectiveness of an inquiry-based short intervention in reducing students’ test anxiety.